The best course available : a personal account of the secret U.S.-Japan Okinawa reversion negotiations - Wakaizumi, Kei, 1930-1996 (University of Hawai'i Press, 2002)
Challenging the silence of the official bureaucracies in Washington and Tokyo, Wakaizumi Kei reveals the truth behind the secret 1969 agreement that ensured the eventual reversion of Okinawa to Japanese jurisdiction in 1972. Revelation of this sec.
"In association with Program on Education and Training, East-West Center."
Keywords: United States -- Foreign relations -- Japan.; Japan -- Foreign relations -- United States.; United States -- Foreign relations -- 1945-1989.; Japan -- Foreign relations -- 1945-1989.; Okinawa Island (Japan) -- History -- 20th century.; Japon -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- 1945-1989.; Japon -- Relations extérieures -- 1945-1989.; Okinawa (Japon : Île) -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Diplomatic relations; Japan; Japan -- Okinawa Island; United States; Onderhandelingen.; Okinawa.; 1900-1999; History